2000
DOI: 10.1159/000030529
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is Diagnostic Imaging in Determination of Size and Multifocality of Renal Cell Carcinoma as a Prerequisite for Nephron-Sparing Surgery?

Abstract: Background: The indication for elective nephron-sparing surgery (NSS) in renal cell carcinoma (RCC) is under discussion in the urological literature. The main problem of NSS is the multifocality of RCC. The presented study was performed to asses the accuracy of pre- and intraoperative ultrasound (US), and computerized tomography (CT) in determination of tumor size and detection of multifocal lesions. Materials and Methods: Tumor size was measured by preoperative US and CT and compared with the tumor diameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…In our study the rate was calculated as 1.6%. Our occult multifocality rate on preoperative imaging of 11.4% is consistent with those demonstrated by other researchers who reported a range of 3.5-13.1% [5,19] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study the rate was calculated as 1.6%. Our occult multifocality rate on preoperative imaging of 11.4% is consistent with those demonstrated by other researchers who reported a range of 3.5-13.1% [5,19] .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, CT and ultrasonography detected 12.5% of multifocality among kidneys with multifocal tumors, preoperatively; this is consistent with published rates of 10-44% [2][3][4][5]19] . However, some researchers have failed to detect multifocality with either ultrasonography or CT [1,6] , while others report 94-95% detection rates using dual-phase helical CT or three-dimensional magnetic resonance imaging [20,21] .…”
Section: Discussionsupporting
confidence: 91%
“…The relationship of multifocality and local recurrence is neither linear nor predictable [7]. Schlichter et al [18] reported that preoperative ultrasound and CT were able to detect multifocal tumors in only 22.9%. So, preoperative routine imaging cannot safely predict multifocal lesions of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…The careful examination of preoperative imaging is crucial to anticipate the potential difficulties of PN [4]. The anatomy, as depicted by cross-sectional imaging, is fragmented into multiple plain images referred to the different sections, projections and phases of the computed tomography (CT) scan.…”
Section: Introductionmentioning
confidence: 99%